2020
DOI: 10.3390/f11090961
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Clear-Cutting of a Boreal Forest on Carbon Dioxide, Methane and Nitrous Oxide Fluxes

Abstract: The 2015 Paris Agreement encourages stakeholders to implement sustainable forest management policies to mitigate anthropogenic emissions of greenhouse gases (GHG). The net effects of forest management on the climate and the environment are, however, still not completely understood, partially as a result of a lack of long-term measurements of GHG fluxes in managed forests. During the period 2010–2013, we simultaneously measured carbon dioxide (CO2), methane (CH4) and nitrous oxide (N2O) fluxes using the flux-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 106 publications
(158 reference statements)
6
23
0
3
Order By: Relevance
“…Clear‐cutting in boreal forests (not after fire) can turn forest soils from sinks to sources of CH 4 due to reductions in evapotranspiration and consequent increases in the water table (Sundqvist et al, 2014; Vestin et al, 2020) or soil compaction by heavy machinery (Strömgren et al, 2016; Teepe et al, 2004). However, we found no significant differences in SWC between the SHM and HM sites, and we did not observe any evidence of soil compaction at the SHM site.…”
Section: Discussionmentioning
confidence: 99%
“…Clear‐cutting in boreal forests (not after fire) can turn forest soils from sinks to sources of CH 4 due to reductions in evapotranspiration and consequent increases in the water table (Sundqvist et al, 2014; Vestin et al, 2020) or soil compaction by heavy machinery (Strömgren et al, 2016; Teepe et al, 2004). However, we found no significant differences in SWC between the SHM and HM sites, and we did not observe any evidence of soil compaction at the SHM site.…”
Section: Discussionmentioning
confidence: 99%
“…12 and 13). Similar results of the soil turning from a CH4 sink to a source after clearcutting have been found on both peat (Zerva and Mencuccini, 2005) and mineral soil (Castro et al, 2000;Vestin et al, 2020) soil, which were attributed to increases in WTL and soil moisture. However, opposing results have also been observed on both soil types.…”
Section: Changes In Ch4 Fluxessupporting
confidence: 76%
“…Large CO2 emissions have been measured for several years after clearcutting upland forests (Amiro et al, 2010;. Also, the net CH4 Vestin et al, 2020) and N2O emissions have been observed to increase, even though the research is not as comprehensive as with CO2. These environmental and economic problems have raised a discussion if continuous cover forestry (CCF) could be a feasible alternative to EM in peatland forests .…”
Section: Introductionmentioning
confidence: 99%
“…Water table variability is likely higher than in the pristine state because lower soil macroporosity and higher bulk density developed after long term drainage have a negative effect on hydraulic conductivity and water storage capacity (Ahmad et al, 2020;Liu et al, 2020;Kreyling et al, 2021). High organic substrate availability is expected due to rewetting associated disturbances, tree residues, turnover of tree roots and its associated microbial biomass and expansion of wetland vascular plants (Rigney et al, 2018;Vestin et al, 2020). High nutrient availability due to low plant nutrient demand is expected which, added to rewetting associated disturbances, might promote high nutrients exports often reported after rewetting (Koskinen et al, 2017;Nieminen et al, 2020).…”
Section: Restoration Phasesmentioning
confidence: 99%